2006
DOI: 10.1099/jmm.0.46199-0
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia cenocepacia utilizes ferritin as an iron source

Abstract: Burkholderia cenocepacia is a member of the Burkholderia cepacia complex, a group of genetically similar species that inhabit a number of environmental niches, including the lungs of patients with cystic fibrosis (CF). To colonize the lung, this bacterium requires a source of iron to satisfy its nutritional requirements for this important metal. Because of the high potential for damage in lung tissue resulting from oxygen–iron interactions, this metal is sequestered by a number of mechanisms that render it pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 34 publications
(30 reference statements)
1
54
0
1
Order By: Relevance
“…Burkholderia cenocepacia is also capable of exploiting the ferritin iron source in the CF lung by protease cleavage (Whitby et al, 2006). Our studies have shown that Burkholderia cenocepacia, in addition to ferritin, also has the ability to utilize lactoferrin and transferrin when siderophore production is unavailable (Tyrrell et al, 2015).…”
Section: Iron Acquisition From Host Iron-binding Proteinsmentioning
confidence: 79%
“…Burkholderia cenocepacia is also capable of exploiting the ferritin iron source in the CF lung by protease cleavage (Whitby et al, 2006). Our studies have shown that Burkholderia cenocepacia, in addition to ferritin, also has the ability to utilize lactoferrin and transferrin when siderophore production is unavailable (Tyrrell et al, 2015).…”
Section: Iron Acquisition From Host Iron-binding Proteinsmentioning
confidence: 79%
“…Ferritin is thought to be degraded by the host cell to meet its own iron needs; Neisseria is able to access the released iron as well (59). In contrast, in Burkholderia cenocepacia, an opportunistic pathogen of cystic fibrosis patients, ferritin degradation and subsequent iron release appear to be directly mediated by a secreted or surface-bound serine protease (60). Ferritin levels are known to be higher in the lungs of people with cystic fibrosis relative to healthy individuals, suggesting a direct link to the pathogenesis of this organism.…”
Section: Bacterial Iron and Heme Acquisition Systemsmentioning
confidence: 99%
“…However, as noted above, certain pathogens are able to circumvent these decreases in available iron by utilizing ferritin as an iron source. Therefore, the increased ferritin in macrophages may ultimately be beneficial to a pathogen, such as B. cenocepacia, that can survive in a macrophage and utilize ferritin (60,108).…”
Section: Alteration Of Host Iron-related Proteins During the Acute-phmentioning
confidence: 99%
“…Preliminary data indicate that HI1369 has a role in heme acquisition (data not shown). In other bacterial species, proteases play a direct role in the acquisition of iron and heme from various sources (12,21,24,28). The FeHm regulon contains genes with no known role in iron/heme uptake.…”
mentioning
confidence: 99%